Patient Perceptions of Hospital Experiences: Implications for Innovations in Patient Safety. Issue 2 (March 2022) - Butler, Jorie M.; Gibson, Bryan; Schnock, Kumiko; Bates, David; Classen, David
Abstract : Objective: The purpose of this study was to qualitatively examine safety experiences of hospitalized patients and families. Methods: We conducted 5 focus groups at 2 sites with patients and family members of patients who had been hospitalized at least once within the preceding 2 years. Using a semistructured focus group script, participants were asked to describe hospital experiences, including any safety risks or problems, and to discuss trust in the hospital care team or members of the care team. All focus groups were audiorecorded and transcribed, and transcriptions were qualitatively analyzed using thematic analysis by experienced qualitative analysts and experts in patient safety. Results: We collected rich descriptions of safety problems in the hospital. We identified 4 main themes from our focus group data. (1) Experiences with safety problems were not unusual among participants, (2) patients and families develop a structured "care story" about their hospital experiences, (3) there is a spectrum of trust between patients and the hospital care team members that can be diminished or enhanced by experiences, and (4) patients believed having someone who could advocate for them during their hospitalization was important. Conclusions: Our results suggest that acknowledgment of safety problems, clear communication, building trust, and a role for advocacy are impactful pathways health care providers and health care systems can improve patient experiences. Information technology such as patient- and clinician-facing displays can support each of these actions.